Downregulation of BK channel function and protein expression in coronary arteriolar smooth muscle cells of type 2 diabetic patients. Issue 1 (30th May 2018) - Lu, Tong; Chai, Qiang; Jiao, Guoqing; Wang, Xiao-Li; Sun, Xiaojing; Furuseth, Jonathan D; Stulak, John M; Daly, Richard C; Greason, Kevin L; Cha, Yong-Mei; Lee, Hon-Chi
Abstract: Aims: Type 2 diabetes (T2D) is strongly associated with cardiovascular morbidity and mortality in patients. Vascular large conductance Ca 2+ -activated potassium (BK) channels, composed of four pore-forming α subunits (BK-α), and four regulatory β1 subunits (BK-β1), are densely expressed in coronary arterial smooth muscle cells (SMCs) and play an important role in regulating vascular tone and myocardial perfusion. However, the role of BK channels in coronary microvascular dysfunction of human subjects with diabetes is unclear. In this study, we examined BK channel function and protein expression, and BK channel-mediated vasodilation in freshly isolated coronary arterioles from T2D patients. Methods and results: Atrial tissues were obtained from 16 patients with T2D and 25 matched non-diabetic subjects during cardiopulmonary bypass procedure. Microvessel videomicroscopy and immunoblot analysis were performed in freshly dissected coronary arterioles and inside-out single BK channel currents was recorded in enzymatically isolated coronary arteriolar SMCs. We found that BK channel sensitivity to physiological Ca 2+ concentration and voltage was downregulated in the coronary arteriolar SMCs of diabetic patients, compared with non-diabetic controls. BK channel kinetics analysis revealed that there was significant shortening of the mean open time and prolongation of the mean closed time in diabetic patients, resulting in a remarkable reduction of the channel open probability. Functional studies showed that BK channel activation by dehydrosoyasaponin-1 was diminished and that BK channel-mediated vasodilation in response to shear stress was impaired in diabetic coronary arterioles. Immunoblot experiments confirmed that the protein expressions of BK-α and BK-β1 subunits were significantly downregulated, but the ratio of BK-α/BK-β1 was unchanged in the coronary arterioles of T2D patients. Conclusions: Our results demonstrated for the first time that BK channel function and BK channel-mediated vasodilation were abnormal in the coronary microvasculature of diabetic patients, due to decreased protein expression and altered intrinsic properties of BK channels.